2016
DOI: 10.1111/cei.12801
|View full text |Cite
|
Sign up to set email alerts
|

Free and complexed-secretory immunoglobulin A triggers distinct intestinal epithelial cell responses

Abstract: SummarySecretory immunoglobulin A (SIgA) antibodies play an important role in protecting the mucosal surfaces against pathogens and maintaining homeostasis with the commensal microbiota. Because a substantial portion of the gut microbiota is coated with SIgA, we hypothesized that microbiota–SIgA complexes are important for the maintenance of gut homeostasis. Here we investigated the relationship between microbiota–SIgA complexes and inflammatory epithelial cell responses. We used a multi‐cellular three‐dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 44 publications
(68 reference statements)
1
36
0
Order By: Relevance
“…Previous studies have shown the involvement of IgA in moderating inflammatory responses through modulating dendritic cells and regulatory T cell functions (61, 62). Further, secretory IgA-commensal complexes were shown to reduce inflammatory responses in intestinal epithelial cells (63). Thus, the role of secretory IgA in mitigating infection-induced inflammatory responses is intriguing and requires further investigation.…”
Section: Effects Of G+ Versus G− Probiotics On Enteric Infections Andmentioning
confidence: 99%
“…Previous studies have shown the involvement of IgA in moderating inflammatory responses through modulating dendritic cells and regulatory T cell functions (61, 62). Further, secretory IgA-commensal complexes were shown to reduce inflammatory responses in intestinal epithelial cells (63). Thus, the role of secretory IgA in mitigating infection-induced inflammatory responses is intriguing and requires further investigation.…”
Section: Effects Of G+ Versus G− Probiotics On Enteric Infections Andmentioning
confidence: 99%
“…It was the first technology used to develop 3-D models for infection studies with bacterial (Salmonella) and viral (rhinovirus) pathogens (11,51). A range of RWV-derived 3-D models have been developed using cell lines, stem cells, and/or primary cells, including small and large intestine (11,80,141,143,145,146,152,(168)(169)(170)(171)(172)(173)(174)(175)(176)(177), lung (144,147,(178)(179)(180)(181)(182), liver (148,153,174,183,184), bladder (8,(185)(186)(187), reproductive tissue (149)(150)(151)(188)(189)(190), heart (191)(192)(193), prostate (142,186,194), pancreas (195,<...>…”
Section: Modeling the Microenvironment: 3-d Models For Infectious Dismentioning
confidence: 99%
“…1B, panel d), polarization, appropriate expression/ localization of adherens/tight junctional complexes, metabolic product secretion, gene expression, cytokine production, responses to antimicrobials and microbial products, support of commensals, and/or susceptibility to infection (8, 11, 80, 141-153, 168-194, 197-208). In addition, RWV models have been advanced to incorporate immune cells to study their role in host-microbe interactions (171,175,177,180).…”
Section: Modeling the Microenvironment: 3-d Models For Infectious Dismentioning
confidence: 99%
See 2 more Smart Citations